2009
DOI: 10.2147/btt.s3769
|View full text |Cite
|
Sign up to set email alerts
|

Review of the safety and efficacy of imiglucerase treatment of Gaucher disease

Abstract: Abstract:Most patients who suffer from symptomatic Gaucher disease will benefit from enzyme replacement therapy (ERT) with imiglucerase. The safety profile is excellent, only a small percentage of those exposed developing antibodies; similarly, very few patients require pre-medication for allergic reactions. Within 3 to 5 years of imiglucerase therapy, best documented at doses of 30 to 60 units/kg/infusion, hepatosplenomegaly can be expected to be reduced so that the liver volume will be maintained at 1 to 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…More extended observation periods are expected to achieve an effect. In addition, it has been recently suggested that GD-specific patient-reported outcome measures (PROM) may be more relevant to showing small, meaningful changes, and these should be used in the subsequent study [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More extended observation periods are expected to achieve an effect. In addition, it has been recently suggested that GD-specific patient-reported outcome measures (PROM) may be more relevant to showing small, meaningful changes, and these should be used in the subsequent study [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 1991, intravenous enzyme replacement therapy (ERT) has become the standard of care, improving almost all GD-related features, improving anemia and thrombocytopenia, reducing organomegaly (liver and spleen), and alleviating skeletal findings [ 5 , 6 , 7 ]. Therapy goals include hematological, visceral, and bone manifestations and improvement in quality of life, fatigue, and social participation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…ERT has emerged as the standard of care for type I GD [8,9]. Over two decades since the introduction of this therapy [10], it has become clear that many of the symptoms and signs of visceral GD respond adequately to ERT [11]. Despite its great success, ERT also has disadvantages, including costly manufacture, inconvenience of the intravenous infusions and the inability of the intravenously administered enzyme to cross the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%